2016
DOI: 10.3389/fpls.2016.01668
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Molecular Characterization of the Prehaustorial Resistance against Wheat Leaf Rust (Puccinia triticina) in Einkorn (Triticum monococcum)

Abstract: Puccinia triticina f. sp. tritici (Eriks.), the causal agent of leaf rust, causes substantial yield losses in wheat production. In wheat many major leaf rust resistance genes have been overcome by virulent races. In contrast, the prehaustorial resistance (phr) against wheat leaf rust detected in the diploid wheat Einkorn (Triticum monoccocum var. monococcum) accession PI272560 confers race-independent resistance against isolates virulent on accessions harboring resistance genes located on the A-genome of Triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(65 citation statements)
references
References 97 publications
(129 reference statements)
5
59
0
1
Order By: Relevance
“…This suggests that H 2 O 2 might initiate HR-defence mechanism. Our results are in line with the observation of Serfling et al (2016) where HR was observed in mesophyll cells that were in contact with fungal haustorial mother cells at 24 hai, and the observed pre-haustorial resistance in the resistant accession PI272560 is due to an early HR of the first infected mesophyll cells. An HR accompanied by H 2 O 2 accumulation also occurs in other interactions of plants with fungal parasites and causes non-host resistance to wheat stripe rust in broad bean (Cheng et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that H 2 O 2 might initiate HR-defence mechanism. Our results are in line with the observation of Serfling et al (2016) where HR was observed in mesophyll cells that were in contact with fungal haustorial mother cells at 24 hai, and the observed pre-haustorial resistance in the resistant accession PI272560 is due to an early HR of the first infected mesophyll cells. An HR accompanied by H 2 O 2 accumulation also occurs in other interactions of plants with fungal parasites and causes non-host resistance to wheat stripe rust in broad bean (Cheng et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This could explain that accumulation of H 2 O 2 in guard cells following recognition of leaf rust structures might be involved in stomatal closure, this being supported by the fact that we observed more accumulation of ABA in plants infected with leaf rust (data no shown), It had been reported that appressoria formation of P. triticina also caused stomata closure in wheat leaves (Bolton et al 2008). Further studies shoe a correlation between H 2 O 2 generation and hypersensitive reaction (HR) in resistance mechanism against wheat rust species (Wang et al 2007; Orczyk et al 2010; Serfling et al 2016). In the current study, the accumulation of H 2 O 2 due to both resistance inducers was observed 24 hai which corresponds to the beginning of haustorium generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This very early detection response of nonself in plants is known as PAMPtriggered immunity (PTI) and is best characterized in model organisms such as rice and Arabidopsis (Meyers et al, 2003;Zhou et al, 2004;Chinchilla et al, 2006;Zipfel, 2008;Ayliffe et al, 2011). Pre-haustorial resistance (PHR) is where fungal growth is terminated before plant cell entry and has proven more durable against biotrophic pathogens (Rubiales & Niks, 1996;Mart ınez et al, 2001;Serfling et al, 2016). PHR led to macroscopic immunity in previous studies in wheat (Anker & Niks, 2001;Serfling et al, 2016) and barley (Hoogkamp et al, 1998;Dracatos et al, 2014Dracatos et al, , 2016, and is a feature of host, near nonhost and nonhost interactions.…”
Section: Mechanisms Of Host and Nonhost Resistance In Plantsmentioning
confidence: 99%
“…Pre-haustorial resistance (PHR) is where fungal growth is terminated before plant cell entry and has proven more durable against biotrophic pathogens (Rubiales & Niks, 1996;Mart ınez et al, 2001;Serfling et al, 2016). PHR led to macroscopic immunity in previous studies in wheat (Anker & Niks, 2001;Serfling et al, 2016) and barley (Hoogkamp et al, 1998;Dracatos et al, 2014Dracatos et al, , 2016, and is a feature of host, near nonhost and nonhost interactions. The best and most widely studied examples of such resistance are mutant or naturally defective alleles of the Mlo locus in barley (Tosa & Shishiyama, 1984).…”
Section: Mechanisms Of Host and Nonhost Resistance In Plantsmentioning
confidence: 99%